Nitrogen and carbohydrate fractions on Tifton-85 pastures overseeded with annual winter and summer forage species in different seasons - Moreira, Andréia Luciane; Berchielli, Telma Teresinha [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP]; Simili, Flávia Fernanda; Fagundes, Jailson Lara; Gomide, Carlos Augusto de Miranda (Sociedade Brasileira de Zootecnia, 2012)
An experiment was conducted during the 2001-2002 winter-spring-summer to determine the nitrogen and carbohydrate fractions in Tifton-85 pastures exclusively or overseeded with oats, millet and sorghum-sudangrass hybrids. The treatments were Tifton-85 overseeded with millet + bristle oat; sorghum-sudangrass + bristle oat, on 06/19/2002 and 07/02/2002, respectively; and Tifton-85 (Control). The experiment was conducted in a randomized block design with three replications. Nitrogen and carbohydrate fractions were affected by the nitrogen and total carbohydrate contents observed in the pasture overseeded at different seeding times, and by the different growth periods. The highest nitrogen fractions (A + B1) were observed in the early growth periods. Overseeding affected the forage nitrogen and carbohydrate fraction contents positively. The high solubility of both carbohydrate and protein from millet + bristle oat and bristle oat + sorghum-sudangrass mixtures indicates the quality of these forages and their potential use as an important supplement in forage systems based on tropical pastures.
Keywords: Bristle oat; soluble nitrogen; Sorghum-sudangrass; total carbohydrate